Drugs that interact with levothyroxine: an observational study from the Thyroid Epidemiology, Audit and Research Study (TEARS). (14th August 2014) - A. Irving, Savannah; Vadiveloo, Thenmalar; Leese, Graham P.
Abstract Objective The aim of this study was to determine the extent of drug interactions affecting levothyroxine, using study drugs often co‐administered to patients on long‐term levothyroxine therapy. Design A retrospective population analysis linking biochemistry and prescription data between 1 January 1993 and 31 December 2012 was used. Patients The study population was Tayside residents prescribed levothyroxine on at least three occasions, within a six‐month period, prior to the start of a study drug. Individuals acted as their own controls pre‐ and postinitiation of study drug. Overall, 10 999 patients (mean age 58 years, 82% female) being treated with thyroxine were included in the study. Measurements Changes in TSH following initiation of study drug. Results Iron, calcium, proton pump inhibitors and oestrogen all increased serum TSH concentration: an increase of 0·22 mU/l (P < 0.001), 0·27 mU/l (P < 0·001), 0·12 mU/l (P < 0·01), and 0·08 mU/l (P < 0·007), respectively. For these four study drugs, there was a clinically significant increase of over 5 mU/l in serum TSH, in 7·5%, 4·4%, 5·6% and 4·3% patients, respectively. There was a decrease of 0·17 mU/l (P‐value 0.01) in the TSH concentration for those patients on statins. The TSH decreased by 5 mU/l in 3·7% of patients. There was no effect with H2 receptor antagonists or glucocorticoids. Conclusion This large population‐based study demonstrates significant interaction between levothyroxine and iron, calcium, proton pump inhibitors, statins and oestrogens. These drugs may reduce the effectiveness of levothyroxine, and patients' TSH concentrations should be carefully monitored.